Improvement in Al-Qur’an Hadith Learning Outcomes Through Kahoot Assisted Time Games Tournament Model - Ervina Uli; Alrudi Yansah; Dedi Yuisman (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
Learning of Al-Qur'an Hadith in schools continues to face several pedagogical challenges, including students’ low learning interest, the dominance of teacher-centered lecture methods, and learning outcomes that frequently fail to meet the established competency standards. Addressing these issues requires an innovative and interactive learning model capable of increasing student engagement and conceptual understanding. This study aimed to improve students’ learning outcomes in the Al-Qur'an Hadith subject, particularly on the topic of Madd recitation rules, through the implementation of the Teams Games Tournament (TGT) cooperative learning model assisted by the Kahoot platform in Class VIII E of MTsN 2 Bungo. The study employed Classroom Action Research based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 26 eighth-grade students. Quantitative data were collected through multiple-choice achievement tests administered at the end of each cycle, while qualitative data were obtained from classroom observations of students’ learning activities and participation. The findings demonstrated a significant improvement in students’ academic achievement and classroom engagement. The mean score increased from 66.7 in the pre-cycle stage to 74.5 in Cycle I and further improved to 83 in Cycle II. Likewise, classical learning mastery improved from 42.3% in the pre-cycle stage to 61.5% in Cycle I and reached 85% in Cycle II, exceeding the predetermined success criterion of 80%. The study concludes that the Kahoot-assisted TGT model is effective in enhancing students’ learning outcomes in Al-Qur'an Hadith learning. The effectiveness of the model was supported by several factors, including appropriate answer duration settings, technical guidance for students, stable internet connectivity, and the provision of rewards to increase motivation